Child Custody Contest: Islamic Jurisprudence and Indonesian Positive Law on Remarried Mothers - Afif Mubaroq; Jumni Nelli; Zulikromi Zulikromi (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study examines child custody rights (hadhanah) under Islamic jurisprudence and Indonesian positive law, focusing on scholarly disagreements regarding the legal consequences of a remarried mother’s custody determination. Research Methodology: This study employs a qualitative library research method, reviewing classical fiqh texts, Indonesian legislation, and jurisprudential literature through a comparative analysis. Results: Scholars are divided into three positions: the majority (jumhur) hold that remarriage automatically forfeits maternal custody; Ibn Hazm argues that custody remains if child welfare is unharmed; and Imam al-Baghawi conditions retention on consent from both the biological father and new husband. Kompilasi Hukum Islam (KHI) does not explicitly address this issue but implicitly supports retaining maternal custody unless the child's well-being is compromised. Conclusions: Indonesian positive law diverges from the majority fiqh position by applying a welfare-based approach, aligning more closely with Ibn Hazm and Imam Al-Baghawi. Clearer statutory regulation is needed to resolve the existing legal vacuum. Limitations: This study relies on qualitative doctrinal analysis without empirical court data, which may limit the generalizability of the findings. Contributions: This study contributes to Islamic family law and Indonesian legal scholarship by clarifying scholarly positions on hadhanah for remarried mothers and highlighting the need for legislative reform aligned with the best interests of the child.